2019
DOI: 10.3390/min9050293
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, Zircon U–Pb Geochronology, and Lu–Hf Isotopes of the Chishan Alkaline Complex, Western Shandong, China

Abstract: Mass alkaline magmatic activities in Western Shandong during the late Mesozoic controlled the mineralization processes of gold and rare earth element (REE) polymetallic deposits in the region. The Chishan alkaline complex is closely associated with the mineralization of the Chishan REE deposit, which, as the third largest light REE deposit in China following the Baiyenebo (Inner Mongolia) and Mianning (Sichuan) deposits, is considered a typical example of alkaline rock mineralization throughout the North China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Frequency diagrams of compiled geochronological ages (Figure 14) show that the magmatic rocks formed by multistage magmatism during the Mesozoic, overlapping the ages of major metalliferous deposits. This spatiotemporal consistency indicates a possible relationship between the formation of gold, molybdenum deposits, and magmatism in the north of the NCC, the magmatism likely provides the thermodynamic condition and the source of metallogenic hydrothermal fluid for mineralization [21][22][23]91]. Combined with previous research results, it has been shown that the Mesozoic endogenetic metalliferous deposits formed in a compressive environment influenced by the subduction of the Paleo-Pacific plate similar to the magma events in the north of the NCC [80,83,92,93].…”
Section: The Causal Link Between the Large-scale Mineralization And Tmentioning
confidence: 74%
See 3 more Smart Citations
“…Frequency diagrams of compiled geochronological ages (Figure 14) show that the magmatic rocks formed by multistage magmatism during the Mesozoic, overlapping the ages of major metalliferous deposits. This spatiotemporal consistency indicates a possible relationship between the formation of gold, molybdenum deposits, and magmatism in the north of the NCC, the magmatism likely provides the thermodynamic condition and the source of metallogenic hydrothermal fluid for mineralization [21][22][23]91]. Combined with previous research results, it has been shown that the Mesozoic endogenetic metalliferous deposits formed in a compressive environment influenced by the subduction of the Paleo-Pacific plate similar to the magma events in the north of the NCC [80,83,92,93].…”
Section: The Causal Link Between the Large-scale Mineralization And Tmentioning
confidence: 74%
“…Also, the granitic magma related to mineralization is of high emplacement without eruption, so that the volatile and the metallogenic elements are well preserved to form the large-scale mineralization in the region. Thus, the fault clefts are always constructions of ore-conducting and ore-bearing structures and in a condition of formation of deposits or ore-bodies [22,23,77,90]. For example, the Wulong Gold Mine in Liaoning province was affected by the Yanshanian tectonic-magmatic.…”
Section: The Causal Link Between the Large-scale Mineralization And Tmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, garnet Sm-Nd dating is conducted on the Hongshan skarn deposits to further constrain the timing of skarn formation in Zu et al [27]. The emplacement ages and geochemical and isotopic signatures of ore-related intrusions are also proved to be genetically linked with the formation of mineral deposits [28][29][30][31][32][33][34].…”
mentioning
confidence: 99%